Synthesis of 3-amino-2-ethoxycarbonyl pyrido[1,2-a]thieno-[2,3-d]-4-pyrimidone derivatives and their antimalarial and cytotoxic activities in vitro - Charris, Jaime (2000)
A series of 3-amino-2-ethoxycarbonyl pyrido[1,2-a]thieno[2,3-d]-4-pyrimidone 10-13 were prepared in order to investigate their cytotoxicity and antimalarial activities. Some of the them showed a promising activity. The detailed synthesis, spectroscopic, computational and biological data are described.